Development of a simulation model of energy-saving system based on CCGT-110 and ABСM for energy and thermodynamic analysis - L. V. Galimova; D. Z. Bayramov (Вестник Дагестанского государственного технического университета: Технические науки, 2021)
Objectives. Simulation modeling is increasingly being used for the study of complex economic, technical, biological, etc. systems. Such systems are characterized by multifactorial relationships of their functioning, nonlinear dependencies between system elements and stochasticity of their parameters, etc. The purpose of this work is to develop a simulation model based on the C# programming language for the energy-saving CCGT-110 and ABCM system based on the results of manual analysis according to the data of a full-scale experiment.Method. Methods of linear and nonlinear approximation, methods of energy and thermodynamic analysis, as well as methods of mathematical simulation modeling are used to develop the simulation model.Result.The result of this work is the developed software SAESS 3.0, which allows you to analyze the operation of the CCGT-110 and ABCM systems together and  separately  in  a  wide  range  of  parameters  and  in  real  time.  Conclusion.To  assess  the adequacy of the developed program, a comparative analysis of software and manual calculation was carried out. Deviations do not exceed an average of 3 %, which confirms the reliability of the simulation model.